2011
DOI: 10.1007/s10067-011-1779-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of switching anti-TNF drugs in rheumatoid arthritis—a study based on observational data from the Finnish Register of Biological Treatment (ROB-FIN)

Abstract: The aim of this study was to assess, based on observational data from the Finnish Register of Biological Treatment, the outcomes of switching an initial tumor necrosis factor (TNF) blocker to another in the treatment of rheumatoid arthritis (RA). RA patients, who started biological therapy with a TNF blocker between May 1999 and April 2009 and who switched to another TNF blocker, were studied (n=479). The outcomes were assessed according to the reason for and type of the switch. Outcome assessments included Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 37 publications
3
38
0
3
Order By: Relevance
“…This difference may be explained by the difference in the accuracy of the thick smear reading and the improvements made in the design of the second generation OptiMal-IT test [17]. Palmer et al [18] and Dolo et al [19] observed results similar to our findings in field studies conducted respectively in Honduras and in Mali with analogous sensitivity, specificity and Kappa concordance. Our thick smears were read by 2 independent readers with one at the field site and a second more experienced reader in the laboratory in Bamako.…”
Section: Discussionsupporting
confidence: 81%
“…This difference may be explained by the difference in the accuracy of the thick smear reading and the improvements made in the design of the second generation OptiMal-IT test [17]. Palmer et al [18] and Dolo et al [19] observed results similar to our findings in field studies conducted respectively in Honduras and in Mali with analogous sensitivity, specificity and Kappa concordance. Our thick smears were read by 2 independent readers with one at the field site and a second more experienced reader in the laboratory in Bamako.…”
Section: Discussionsupporting
confidence: 81%
“…A recent cohort study suggested a better effectiveness of switching to an alternative aTNF after secondary failure than primary failure which supports our findings. However, it did not compare aTNF with non-aTNF-Bio discontinuation rates 12. Pathophysiological mechanisms of primary failure remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…There are currently limited trial data to inform this decision, so this issue has been addressed mainly using observational data from registries and similar studies. These data suggest that sequential switching to an alternative TNF inhibitor will reduce disease activity and improve functional scores, but that response rates, probability of response, and drug survival are all lower than with first anti-TNF agent (Gomez-Reino and Carmona, 2006;Hyrich et al, 2007;Virkki et al, 2011;Chatzidionysiou et al, 2014). The best results were seen with switches from infliximab to etanercept for reasons of secondary inefficacy (Chatzidionysiou et al, 2014).…”
Section: A Anti-tumor Necrosis Factor Drugs In Rheumatoid Arthritismentioning
confidence: 99%